2023
DOI: 10.24875/gmm.m21000576
|View full text |Cite
|
Sign up to set email alerts
|

Commute times and audiometric findings among adult population in Mexico City

Abstract: Introduction: Long commute times are common in big cities. Objective: To determine hearing thresholds and their association with commute time in Mexico City. Methods: Cross-sectional study that included 177 healthy adults from 2009 to 2011. Demographic information and commute times were recorded. Hearing was assessed by audiometry. Regression models were constructed to determine the predictors of hearing thresholds. Results: There were 101 men (53%) and 76 women (43%). Mean commute time was 43 minutes (1-150 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…To help corroborate self-report data, we conducted objective sound level measurements in typical work areas and confirmed that mean noise levels in the field did not exceed recommended levels, thereby minimizing the effect of noise exposure as a confounder. However, it is not possible to completely rule out the possibility that environmental noise exposure (Juárez-Pérez et al 2021), as well as genetics or other factors contributed to hearing loss in this sample. This consideration is particularly important given that joint exposure to lead and noise at moderate and high levels have been found to interact with each other (Castellanos & Fuente 2016).…”
Section: Discussionmentioning
confidence: 89%
“…To help corroborate self-report data, we conducted objective sound level measurements in typical work areas and confirmed that mean noise levels in the field did not exceed recommended levels, thereby minimizing the effect of noise exposure as a confounder. However, it is not possible to completely rule out the possibility that environmental noise exposure (Juárez-Pérez et al 2021), as well as genetics or other factors contributed to hearing loss in this sample. This consideration is particularly important given that joint exposure to lead and noise at moderate and high levels have been found to interact with each other (Castellanos & Fuente 2016).…”
Section: Discussionmentioning
confidence: 89%
“…The focus of this study is to analyze infections and mortality associated with the COVID-19 pandemic in Mexico, taking data from the metropolitan area of the valley of Mexico, the largest regional metropolitan area in North America, which represents approximately 20% of the country's population [12] . Our aim is to describe the complete panorama for hospitalized young children ages 0-9 years, as they represent some of the most vulnerable populations in terms of vulnerability to infections.…”
Section: Introductionmentioning
confidence: 99%
“…The Metropolitan Area of the Valley of Mexico is the largest metropolitan area in North America; it is the country's most important economic, political, and social hub. It houses over 22 million people, roughly 20% of the country's population ( 1 ). Given the size and importance of this area, the federal government has devoted much of the national healthcare system's resources to tackling many public health issues.…”
Section: Introductionmentioning
confidence: 99%